Key Success Factors For Implementing Sport For Development Projects in Botswana-A Case For Sport For Life Botswana Project. - Matolela, Kelebogile (Πανεπιστήμιο Πελοποννήσου, 2024)
This study was carried out to establish in relation to the ‘Sport for Life Botswana project’, what different stakeholder representatives’ understandings are, of what the project is designed to achieve, and how the project achievements are identified and evaluated. Project stakeholders’ common understanding of the context and priorities of the project is vital to sustainable project success. Evaluating a project is also a key project management element as it helps to validate if the project produced the expected outcomes and impact among the target population, and provides evidence on the project’s success. This study aims to identify similarities or differences of stakeholder views through the lens of a logic model, and to analyse the goals and objectives of the project as perceived by members of different stakeholder groups. The logical framework also allows the study to tabulate the stakeholders’ perceptions of project inputs, project activities, project outputs, project outcomes, and impact, so to identify causal factors bringing about desired change. The study will also explore an evaluation framework that the organisation responsible for the implementation of the project of study can employ. The evaluation framework would encompass evaluation approaches and methods, and would highlight the strengths and shortcomings of each approach. Currently, there is inadequate knowledge concerning the influence of evaluation on project success, an issue that this study addresses. The study uses primary data from interviews and secondary data from project documents, hence thematic and content analysis are used to analyse the data and draw conclusions from findings. The results provided support for claims that the project within its stipulated lifespan yielded significant outcomes and positively impacted the socio-economic lives of its target group and communities, however a few targets with regards, for example, to gender representation of female participants were not attained.
Keywords: Διαχείριση έργου - Μποτσουάνα; Διαχείριση χρόνου; Ομάδες στο χώρο εργασίας; Προγραμματισμός παραγωγής; Project management - Botswana; Time management; Teams in the workplace; Production scheduling; Logic approach; Projects; Stakeholders; Common understanding; Evaluation